LATE OLIGOCENE THOLEIITIC LAVA FROM KENANGA RIVER, TEGALOMBO PACITAN, EAST JAVA - Dian Novia Sartika; I Wayan Warmada; Bhakti H. Harahap; Widiasmoro Soewondo (Geological Engineering Department Universitas Gadjah Mada, 2009)
Watupatok Formation in Pacitan area consists of lava with basaltic composition and pillow structure. Kenanga river is only 5 km to southeast Watupatok village as type locality of this formation. Kenanga river’s lava were varying from diabasic with paving surface and columnar joint structure to basaltic composition with pillow structure. Lava were found as effusive flow and dike with sandstone inclusion. In field observation, lava exhibits strong porphiritic to aphyric texture, with vesicular to amygdaloidal structure. Plagioclase as phenocryst has mediumsized (2-4 mm) surrounded by volcanic glass as groundmass. Petrographic analysis shows intersertal to hyalophilitic texture, consist of plagioclase, pyroxene and opaque minerals as phenocryst and also groundmass together with volcanic glass. Seconday minerals are quartz, zeolite and calcite. Geochemichal analysis results indicate a low TiO2 (0.8– 0.9 wt.%), medium to high Al2O3 (14–17 wt.%), high Fe2O3 (10–12 wt.%) and low Mg value (Mg#) (39–42). According to TAS and AFM diagram, the rocks is apparently to be basalt and tholeiitic island arc magma. While spidergram pattern of the trace elements shows relatively flat fo HREE and enriched pattern on LREE. Niobium element displays a depleted anomaly, indicated that the crust influences in parental magma, which is another characteristic of magmatic island arc. Based on regional tectonic, the volcanic rocks from Late Oligocene in the area has relationship with subduction processes between Indo-Australia plate and Eurasian plate.Keywords: Pillow structure, tholeiitic, lava, subduction